The Impact of Lipoprotein-Associated Oxidative Stress on Cell-Specific Microvesicle Release in Patients with Familial Hypercholesterolemia. (27th January 2016) - Nielsen, M. H.; Irvine, H.; Vedel, S.; Raungaard, B.; Beck-Nielsen, H.; Handberg, A.
Abstract : Objective . Microvesicles (MVs) are small cell-derived particles shed upon activation. Familial hypercholesterolemia (FH) particularly when associated with Achilles tendon xanthomas (ATX) predisposes to atherosclerosis, possibly through oxLDL-C interaction with the CD36 receptor. To investigate the hypothesis that MVs derived from cells involved in atherosclerosis are increased in FH and that CD36 expressing MVs (CD36+ MVs) may be markers of oxLDL-C-induced cell activation, cell-specific MVs were measured in FH patients with and without ATX and their association with atherogenic lipid profile was studied. Approach and Results . Thirty FH patients with and without ATX and twenty-three controls were included. Plasma concentrations of MVs and CD36+ MVs derived from platelets (PMVs), erythrocytes (ErytMVs), monocytes (MMVs), and endothelial cells (EMVs), as well as tissue factor-positive cells (TF+ MVs), were measured by flow cytometry. Total MVs, MMVs, EMVs, ErytMVs, and TF+ MVs were significantly increased in FH patients, compared to controls. CD36+ MVs derived from endothelial cells and monocytes were significantly higher in FH patients and oxLDL-C predicted all the investigated cell-specific CD36+ MVs in FH patients with ATX. Conclusions . MVs derived from cells involved in atherosclerosis were increased in FH and may contribute to elevated atherothrombosis risk. The increased cell-specific CD36+ MVs observed in FH may represent markers of oxLDL-C-induced cell activation.